Liberating parents from guilt: a grounded theory study of parents' internet communities for the recognition of ADHD. Issue 1 (1st January 2019) - Dauman, Nicolas; Haza, Marion; Erlandsson, Soly
ABSTRACT: Purpose : This study presents a qualitative analysis of information posted on the Internet by two communities of French parents promoting the recognition of ADHD in the context of current health and school practices. Method : Grounded Theory (Strauss & Corbin's approach) was applied to the posted messages, with the aim to discover the main concern and common theme through a constant comparison analysis. Results : Liberating parents from feeling responsible for their child's misconduct was found to be the core category. From this perspective, we account for the commitment of the digital communities to formalize the child's conduct as a consequence of a neurodevelopmental disorder. This approach helps to account for the promotion of behavioural expertise and conditioning strategies (e.g., positive reinforcement) for handling the child's so-called disorder as appropriate parental responses. Giving evidence for parenting struggles was the third main concern of the communities, in the face of perceived skepticism from professionals towards ADHD as a medical condition. Conclusions : By using examples from countries that are found to have a more pro-medical approach to ADHD, the communities aim at improving such medical practices in France. Issues surrounding the claim that ADHD would require a specific style of parenting are also discussed.